The Psychometric Properties of the Norwegian version of Kinder Lebensqualität Fragebogen KINDL®, 2. edition - Rasmussen, Lene-Mari Potulski; Liebenberg, Kaja Bøyesen (PsykTestBarn, 2024)
Description: The Kinder Lebensqualität Fragebogen (KINDL®) is a questionnaire to measure the quality of life in children and adolescents (3-17 years). The questionnaire was developed in Germany and was revised in 1998 by Ravens-Sieberer and Bullinger. It was translated into Norwegian in 2004 by Thomas Jozefiak and Sølvi Helseth. KINDL® includes a self-report version for children and a parent/proxy version with different age- appropriate versions. There are no formal requirements for test administration and interpretation of the test. The questionnaire consists of 24 questions divided into six subscales. An average score is calculated for each subscale as well as for the total scale, which is transformed into a 0-100 score. A high score indicates a high quality of life. Literature search: The literature search resulted in 39 publications that were reviewed in full text, of which 22 were included. Most of the studies reported results from clinical and non- clinical subgroups, while the remaining publications represented the normal population. Psychometrics: Reliability shows good to excellent internal consistency on the total scale for children, but greater variation on the subscales, especially among the youngest children. The test-retest on the total scale with two-week intervals showed a high intraclass correlation coefficient, with lower coefficients for the subscales, particularly in the youngest group. There is limited information on proxy-reporting, but the existing data shows satisfactory reliability. Informant discrepancies generally showed high variations between informants. There are some supports for construct validity, but the factor structure has not been adequately replicated. Correlations with other instruments that also measure quality of life suggest that KINDL® effectively measures what it is intended to measure. Sensitivity to change, is reported as satisfactory. Conclusion: KINDL® appears to be a promising instrument for assessing the quality of life in children and adolescents, both in clinical and non-clinical subgroups, as well as in the general population. KINDL® has moderate documentation of its psychometric properties. The total scale appears reliable for all age groups. However, there is variation among the subscales, which are found to be more suitable for older children than for the youngest (under 12 years). The current data on statistical norms is somewhat limited and becoming outdated.